Effects of Urbanization toward Communities Surrounding Khon Kaen University : Case Study of Ban Non Muang Community, Village No. 12, Sila Sub-district Municipality, Khon Kaen Province - Srikanjun, Preyakan; Sripokangkul, Assoc. Prof. Dr. Siwach (Journal for Developing the Social and Community, 2019)
The purposes of this research were to : 1) study changes of community resulting from urbanization; and 2) study effects of urbanization toward communities surrounding Khon Kaen University, especially Ban Non Muang Community, Village No. 12, Sila Sub-district Municipality, Khon Kaen Province because it is a community located mostly adjacent to Khon Kaen University. This research is qualitative research and applies in-depth interview with key informants. The findings revealed that : After Khon Kaen University was established to extend development to regions under the Fifth National Economic and Social Development Plan, Baan Non Muang has been growing and changes found in the community including land utilization, living and population. These positively and negatively affect the community in terms of economy and society as follows. The positive effect to the society is that community can better access to infrastructure; however, quality of living declines as they face several problems, for example, traffic congestion, water pollution and economy. The land utilization has changed from agricultural purpose to business purpose as the locals sell land to investors for apartment, housing development and commercial buildings. As a result, the occupation has changed from agriculture to business, trade and service accommodating demands of students and university personnel. Besides, investors heavily buy land pieces for profit speculation resulting in much expensive land price.